1.12 Å resolution crystal structure of the catalytic domain of the plasmid‐mediated colistin resistance determinant MCR‐2. Issue 8 (1st August 2017) - Coates, Katie; Walsh, Timothy R.; Spencer, James; Hinchliffe, Philip
Abstract : The crystal structure of the plasmid‐mediated colistin resistance determinant MCR‐2 has been determined at 1.12 Å resolution. This high‐resolution structure highlights the molecular diversity of clinically relevant MCR proteins and provides an accurate starting model for further mechanistic, and in particular computational, studies. Abstract : MCR‐2 confers resistance to colistin, a `last‐line' antibiotic against extensively resistant Gram‐negative pathogens. It is a plasmid‐encoded phosphoethanolamine transferase that is closely related to MCR‐1. To understand the diversity in the MCR family, the 1.12 Å resolution crystal structure of the catalytic domain of MCR‐2 was determined. Variable amino acids are located distant from both the di‐zinc active site and the membrane‐proximal face. The exceptionally high resolution will provide an accurate starting model for further mechanistic studies.